Implementation of the Rules of Procedure of the Regional House of Representatives at the Office of the Regional House of Representatives of North Sulawesi Province - Jetty E. H. Mokat; Sry A. N. Situmorang; Jesica Karouw; Hermon M Karwur; Evi E. Masengi; Muhamad Isa Ramadhan (Technium Social Sciences Journal, 2024)
The title of this research is "Implementation of DPRD Code of Conduct at the North Sulawesi Provincial DPRD Office". The research aims to find out and describe the process of resolving violations of the code of ethics carried out by the Honorary Board in the implementation of the DPRD Standing Orders at the North Sulawesi Provincial DPRD Office. The research method used was qualitative with data collection techniques through observation, interviews, documentation and secondary data analysis. The results showed that the implementation of the rules related to the process of resolving violations of the code of ethics in the DPRD of North Sulawesi Province had been implemented but not maximized, because: The enforcement of sanctions carried out by the Honorary Board has been implemented in accordance with the procedures and the results of the agreement decided in the plenary session, but the sanctions given do not have a deterrent effect on board members who violate the code of ethics. Sanctions given for violators of DPRD rules of conduct should be more firm and real.